Increasing access to education for refugees in Uganda - Muyenga, Mugerwa-Sekawabe (Academy of Science of South Africa, 2021)
This article investigates the scope of the right to education as enjoyed by refugees in terms of domestic (Ugandan), regional (African) and international law. One of the main obstacles to accessing education for refugees in Uganda is financial constraints, which the principle of burden sharing seeks to ameliorate in refugee hosting countries in the Global South. This principial of burden sharing lies at the heart of the Global Compact on Refugees (GCR) which was adopted by the United Nations General Assembly to realize a more equitable distribution of refugee populations, who are disproportionately found in the Global South within States whose financial resources are severely strained. This article explores whether the GCR will increase access to the right to education of refugees in such a country, namely, Uganda. This right is considered to be a "multiplier" right as the degree of access to education impacts the level of enjoyment of other human rights. The article considers whether the international and regional frameworks are likely to increase access to education for refugees in Uganda. Finally, recommendations are made to other stakeholders, namely, the Ugandan government and the United Nations High Commissioner for Refugees (UNHCR), on how to facilitate access to education for refugee children in Uganda.